Factors Affecting the Quality of Earnings (Empirical Study of Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2018-2020) - MINANARI, Minanari; ASMARA, Rina Yuliastuty (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study examines the effect of Tax Planning, Corporate Social Responsibility (CSR), Company Size, and Leverage on Earning Quality (Empirical Study of Transportation Sub Sector Companies Listed on the Indonesia Stock Exchange in 2018-2020). The object of this study is to use a transportation company listed on the Indonesia Stock Exchange (IDX). The research sample was 10 of the 46 companies that met the criteria. The sampling technique used in the study was the purposive sampling method. The results of this study indicate that (1) Tax Planning has no significant negative effect on Earnings Quality, (2) Corporate Social Responsibility (CSR) has a significant negative effect on Earnings Quality, (3) Firm size has a significant negative effect on Earning Quality, (4) Leverage has no significant negative effect on Earnings Quality.